Pengaruh Kualitas Pelayanan terhadap Kepuasan Nasabah di PT Pegadaian (Persero) Cabang Cikampek - Siti Syafaat; Agus Sumitra (BADAN PENERBIT STIEPARI PRESS, 2025)
PT Pegadaian (persero) is a non-banking financial services company in Indonesia that is controlled by the state and operates on a pawn system to provide loans to the general public. Analysis of service quality and customer satisfaction is very necessary, companies must be able to develop customer-oriented marketing concepts. The research objective is to determine the effect of service quality and customer satisfaction. The research method used is quantitative, with data collection through questionnaires to respondents. The research population is active customers of Ultra Micro Creation products from March to April 2024, totaling 177 people, obtained a sample of 64 respondents calculated using the Slovin formula. Based on simple linear regression analysis and forecasting, a significant value of 0.03 (<0.05) was obtained, which indicates that service quality has a significant influence on customer satisfaction. The correlation coefficient test results show a value of 0.25, while the determination test results in an R square value of 0.0522 or 5.22%. This means that service quality affects customer satisfaction by 5.22%, while the remaining 94.78% is influenced by other factors.